Studi Deskriptif terhadap Teknik Pengelasan SMAW pada Praktikum Taruna Teknika AMN Cilacap - Immawan Insani; Priyani Budiyarti (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to describe the implementation of Shielded Metal Arc Welding (SMAW) techniques in practical training conducted by cadets of the Teknika Study Program at AMN Cilacap. The method employed is descriptive quantitative using a Likert-scale questionnaire (1–5). The research sample consisted of 40 second-semester cadets selected through purposive sampling. The questionnaire was structured based on four aspects: theoretical understanding, practical skills, compliance with safety procedures, and perceived obstacles. The results show that theoretical understanding was at a high level (average score of 4.1; 87.5%), practical skills were categorized as adequate (75%), and compliance with safety procedures was very high (90%). However, obstacles were still significantly perceived, with an average score of 2.88 and only 27.5% of respondents giving positive responses. The main obstacles faced by cadets included limited welding equipment, insufficient training in specific welding positions, and inadequate practice time. This study recommends improvements in practical facilities, diversification of training in various welding positions, and more effective management of practice schedules to support optimal learning outcomes.